Comparing Balance Control Between Soccer Players and Non-Athletes During a Dynamic Lower Limb Reaching Task. Issue 1 (2nd January 2020) - Snyder, Natalie; Cinelli, Michael
ABSTRACT: Background : Balance control is an essential element of locomotion that enhances biomotor abilities and physical performance. Individuals with extensive soccer experience display superior static single leg balance control compared to athletes of other sports as well as non-athletes. However, during a match, players often encounter greater challenges to single leg balance that require rapid decision-making skills and dynamic stability. Purpose : The purpose of this study was to determine if individuals with extensive soccer training demonstrate superior single-leg balance control compared to non-athletes during a dynamic lower limb reaching task. Method : 22 varsity soccer players were matched with 21 non-athlete controls. Single-leg balance control was assessed during a Go/No-Go lower limb reaching task. Centre of pressure displacement (dCOP) was measured for both the dominant and non-dominant feet and compared between groups. Results : Soccer players displayed reduced dCOP during All Go trials compared to non-athletes, particularly in the medial-lateral plane. Additionally, soccer players displayed reduced anterior-posterior dCOP during Go/No-Go trials compared to non-athletes, particularly on their dominant foot. Conclusion : Athletes with soccer-specific training demonstrate improved executive control and use of proprioceptive information, which results in an improved ability to maintain single-support balance and corral COP during a dynamic visuomotor lower limb-reaching task. As such, balance training may be a useful addition to athlete training regimes to improve sport-specific performance. Future research would compare these results to athletes of other sports to explore balance control during a visuomotor reaching task and how it may differ based on sport training history.